Evaluation of the effect of olive extracts on blood pressure and cardiovascular health markers in adults: Findings from a double-blind, placebo-controlled, randomised trial - Stef Lauwers; Annelies Breynaert; Annelies Verlaet; Erik Fransen; Tijs Bringmans; Lynn Roth; Emmy Tuenter; Johan Bosmans; Nina Hermans (PLoS ONE, 2026)
Despite advances in reducing cardiovascular disease (CVD) incidence, CVD mortality has increased, emphasising the need for new preventive strategies. Polyphenol-rich olive extracts have been proposed to lower blood pressure by reducing oxidative stress and enhancing nitric oxide production. This double-blind, placebo-controlled, randomised study aims to examine whether a standardised olive extract can lead to a reduction in blood pressure, lipid levels, and biological markers of oxidative stress after supplementation in the context of primary CVD prevention. In this trial, 56 participants with a systolic blood pressure ≥ 130 mmHg received capsules containing 440 mg olive dry extract (123.5 ± 9.4 mg oleuropein, 25.0 ± 3.8 mg hydroxytyrosol) or placebo on a daily basis over eight weeks. Both groups showed significant reductions in systolic blood pressure with a larger decrease in the intervention group as compared to the control group (intervention: −8.3 ± 2.2 mmHg, control: −7.3 ± 2.2 mmHg). However, this decrease was not found significantly different between the two groups. Moreover, total cholesterol, LDL, and apo B levels decreased in both groups, but with no significant difference between them. These results indicate that the olive extract was well-tolerated, although no significant hypotensive benefit was observed, with effects paralleling typical placebo responses in hypertension trials. Literature reports conflicting results on the hypotensive effect of olive polyphenols, indicating the need for further research with well-designed clinical trials. This trial was registered on Clinicaltrials.gov in April 2021, ID NCT04874961.